2020
DOI: 10.21037/jtd-20-761
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of sternoclavicular joint infections: a literature review

Abstract: The sternoclavicular joint (SCJ) is anatomically and clinically significant considering its proximity to important neuro-vascular structures like the subclavian vessels and the phrenic nerve. Infections of this joint masquerade multiple disorders, delay diagnosis and spread to the bone and deep tissues. There is no standardized workup and treatment protocol for sternoclavicular joint infections (SCJI) as defined in literature. Here, we review the existing literature to understand the current knowledge of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 91 publications
0
33
0
Order By: Relevance
“…The abnormalities in the other three patients included joint space widening, presence of a soft tissue shadow, and evidence of osteolysis in the clavicle [ 1 ]. It can take up to 12 days for a CXR to reveal soft tissue swelling [ 18 ]. Our patient's first imaging was a CXR and was negative for any acute findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormalities in the other three patients included joint space widening, presence of a soft tissue shadow, and evidence of osteolysis in the clavicle [ 1 ]. It can take up to 12 days for a CXR to reveal soft tissue swelling [ 18 ]. Our patient's first imaging was a CXR and was negative for any acute findings.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 10 patients with SCJ septic arthritis revealed that 2 to 11 radiological tests were needed to establish the diagnosis, and that CT or MRI was needed in all patients [ 18 ]. MRI as the initial diagnostic test had the best sensitivity, and can show changes within one to two days with no diagnostic delay.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic regimen was changed from ampicillin-sulbactam to amoxicillin-clavulanate on day 15. 1 Her CT on day 20 showed resolution of the extrapleural and mediastinal abscesses, and a decrease in the extent of her sternoclavicular joint abscess. She was discharged on day 22.…”
Section: Figurementioning
confidence: 93%
“…It can spread by direct extension into a neighbouring structure through the space formed by the cervical fascia. 1 Common risk factors include an immunocompromised host, diabetes mellitus, trauma, infection at a distant site and intravenous drug use. 2 We present a case of sternoclavicular joint septic arthritis during regular steroid use, which resulted in mediastinitis through the pretracheal space despite early puncture drainage.…”
Section: Descriptionmentioning
confidence: 99%
“…Sternoclavicular joint infection is a rare form of septic arthritis caused by infectious seeding via the hematogenous route or by direct contiguous spread [ 1 3 ]. The infection can spread to surrounding structures via the lymphatic vessels or by direct extension [ 4 , 5 ], causing serious complications, such as osteomyelitis (56%), abscess formation (25%), and mediastinitis (13%) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%